The ABC of XYZ : understanding the global generations - McCrindle, Mark (UNSW Press, 2009)
Based on a more than a decade of research, this reference is designed for marketers, managers, educators, and parents who need a useful, fun, not-too-technical introduction to generational research. The breezy vocabulary of this kind of study is familiar to most people, Are Gen X-ers still slackers? Will Gen Y-ers ever move out of the house? Why are Zeds so spoiled?, but this guide goes deeper with explanations of how a generation is defined and the statistical tools that allow social scientists to track the behavior of its members over time. The discussion also provides examples of generational conflicts in school, home, and the workplace, and reveals how these clashes can be understood and resolved. Interspersed with useful tables and figures, the book also compares English-speaking countries with their generational counterparts in Japan, Finland, and other parts of the world.